Role of Tyrosine Phosphorylation in PEP1 Receptor 1(PEPR1) in Arabidopsis thaliana - Jae-Han Choi; Man-Ho Oh (Plants)
Leucine-rich repeat receptor-like kinases (LRR-RLKs) have evolved to perceive environmental changes. Among LRR-RLKs, PEPR1 perceives the pep1 peptide and triggers defense signal transduction in Arabidopsis thaliana. In the present study, we focused on PEPR1 and PEPR2, which are the receptors of pep1, to understand the role of tyrosine phosphorylation. PEPR1-CD (cytoplasmic domain) recombinant protein exhibited strong tyrosine autophosphorylation, including threonine autophosphorylation. We subjected all tyrosine residues in PEPR1-CD to site-directed mutagenesis. The recombinant proteins were purified along with PEPR1-CD, and Western blotting was performed using a tyrosine-specific antibody. Among the 13 tyrosine residues in PEPR1-CD, the PEPR1(Y995F)-CD recombinant protein showed significantly reduced tyrosine autophosphorylation intensity compared to PEPR1-CD and other tyrosine mutants, despite little change in threonine autophosphorylation. To confirm the autophosphorylation site, we generated a phospho-specific peptide Ab, pY995. As a result, Tyr-995 of PEPR1-CD was a major tyrosine autophosphorylation site in vitro. To understand the function of tyrosine phosphorylation in vivo, we generated transgenic plants, expressing PEPR1-Flag, PEPR1(Y995F)-Flag, and PEPR1(Y995D)-Flag in a pepr1/2 double mutant background. Interestingly, the root growths of PEPR1(Y995F)-Flag and PEPR1(Y995D)-Flag were not inhibited by pep1 peptide treatment, compared to Col-0 and PEPR1-Flag (pepr1/2) transgenic plants. Also, we analyzed downstream components, which included PROPEP1, MPK3, WRKY33, and RBOHD gene expressions in four different genotypes (Col-0, PEPR1-Flag, PEPR1(Y995F)-Flag, and PEPR1(Y995D)-Flag) of plants in the presence of the pep1 peptide. Interestingly, the expressions of PROPEP1, MPK3, WRKY33, and RBOHD were not regulated by pep1 peptide treatment in PEPR1(Y995F)-Flag and PEPR1(Y995D)-Flag transgenic plants, in contrast to Col-0 and PEPR1-Flag. These results suggest that specific tyrosine residues play an important role in vivo in the plant receptor function.